POWERPOINT SEBAGAI ALAT EDUKASI DALAM BIDANG KESEHATAN - Mikha Masinambow; Ekaristy Mokoagow; Mutiara Nelwan; Asih neyla syam; Nazwita Mahmud; Queen Watuseke; Tamara Ramdhania; Meilifia Tipal; Alya Katili; Syalomitha M. Tatilu; Revalina Nadin Lumuko1; Reivanly mandang; Novita Elmi (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2024)
PowerPoint is software developed by Microsoft and is part of the Microsoft Office package. PowerPoint is designed for creating slide-based presentations. This PowerPoint is widely used in various fields, including education, business, and training, to convey ideas and information in a structured and engaging way. PowerPoint allows its users to create presentations using slides that can contain text, images, graphics and videos. In PowerPoint there are also features such as transitions, animations and templates which function to help enrich the appearance of presentations for its users.